Adaptation and validation of the academic stress inventory scale for college students - Ananda Humaidah; Rachmat Mulyono; Nabila Salsyabila; Navila Auvaizah; Rahma Zikra (Jurnal Psikologi Tabularasa, 2026)
Research on academic stress in Indonesia tends to face limitations in measurement instruments. This is due to the relatively limited number of studies adapting academic stress scales into Bahasa Indonesia, particularly for university student populations. This study aimed to adapt and evaluate the validity of the Academic Stress Inventory as a psychological measurement tool applicable within the educational context. The adapted scale was based on Lin and Chen’s theory of academic stress, encompassing seven dimensions: teacher stress, result stress, test stress, studying in group stress, peer stress, time management stress, and self-inflicted stress, comprising a total of 34 items. The participants in this study were 439 university students. Construct validity was examined using Confirmatory Factor Analysis (CFA) with Mplus 7. The results indicated that the measurement model demonstrated good fit (RMSEA = 0.04), confirming that the scale adequately measures academic stress. Furthermore, all items showed t-values greater than 1.96, indicating that each item was statistically significant and valid. The implication of this study is that the adapted Academic Stress Inventory can be utilized as a valid instrument to measure academic stress in future research contexts involving Indonesian university students.